Pengaruh Pertumbuhan Laba dan Dana Syirkah Temporer terhadap Maqashid Syariah pada Bank Umum Syariah Periode 2021-2023 (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
The purpose of the study was to see the effect of profit growth and temporary syirkah funds with Maqasyid Syariah in 2021-2023. Maqasyid Syariah can be interpreted as ownership of a company that can be seen from the value of its shares. While Bank Umum Sariah can be interpreted as a bank that operates based on Sharia principles and all its operations are based on the Quran and Hadith and there is a halal guarantee in its transactions. The methods used are quantitative verification and descriptive. With a total sample of 24. The results of this study are the Probability Value of X1 (Profit Growth) > 0.5 with a Coefficient value of -0.0001, meaning that the variable X1 (Profit Growth) has no effect on Maqasyid Syariah. The Probability Value of X2 (Temporary Syirkah Funds)
Keywords: Company Value; Profit Growth; Temporary Syirkah Fund.